The Production of Siamese Catfish (Pangasius Sucthii) Intensive Cultivation In Terms of the Nature Physic Pool of Red-Yellow Podzolic, at Different Ages - Sahnan '; Niken Ayu Pamukas; Syafiadiman ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted from April until July 2015 which is located on the village of Patin Koto Mesjid, Kampar, Riau and the Enviromental Quality Laboratory Cultivation, Faculty of Fisheries and Marine Sciences University of Riau. This research was used experimental method, by using a Completely Randomized Design (CRD) (Sudjana, 1991). Then, it is used 4 levels of the treatment (P1, P2, P3,and P4). The research procedure in this study are : 1) The choice of location which is suitable with the desired of pool age; 2) Making the sample of test; 3) measuring several parameters of the quality of soil physical. The result showed that the age of a different pool influence on some parameters of physical properties of soil and water quality parameters during the research. Besides that, during the research it is found the best treatment for pH parameters contained in P2 treatment ranges from 6.56-6.71, Parameter BV best soil treatment is at the treament P2 it is ranged 1.69-1.49g/cm3 for the treatment of texture parameters P1,P2,P4 soil fraction is Clay Loam Sandy and Clay soil fraction for P3, for the parameters soil color of the treatment P1, P2 Dull yellow orange P3, P4 Grayish yellow brown.Keywords: Pangasius sucthii, Red Yellow Poszolic